The Impact of Foreign-direct Investment on Economic Growth in Malaysia: The Role of Financial Development - Alzaidy, Ghaith; Ahmad, Mohd Naseem Bin Niaz; Lacheheb, Zakaria (International Journal of Economics and Financial Issues, 2017)
This paper investigates the impact of foreign-direct investment (FDI) and financial development on economic growth in Malaysia over the period of 1975-2014. According to ARDL bound test approach to co integration analyses, the results found that financial development plays an essential role in mediating the impact of FDI on economic growth in Malaysia. This implies that well-developed financial sectors lead to further and facilitate FDI spillover and hence yield economic growth, particularly for the case of Malaysia. Keywords: Financial development, economic growth, FDI, PCA, ARDL JEL Classifications: F23, O16, O40